On the nature of effective CIO/CEO communication : evidence from an interview study - Hütter, Alexander; Arnitz, Thomas; Riedl, René (Springer Nature, an imprint of Springer International Publishing, 2017)
This book examines the effectiveness of communication between chief information officer (CIO) and chief executive officer (CEO) and its impact on the role of information technology (IT) in an organization. The book is empirically based on interviews with CIO/CEO pairs from twelve organizations in the manufacturing and retail industries. It examines how CIOs and CEOs can achieve effectiveness in their communication, including insights into antecedents and consequences of communication effectiveness. Based on the interview data the authors develop a CIO/CEO communication model with which CIOs and CEOs can gain new insights into the efficiency of their interactions, likely resulting in higher levels of shared understanding regarding the role of IT in their organization.
Keywords: Chief executive officers -- Research -- Case studies.; Chief information officers -- Research -- Case studies.; Interpersonal communication -- Research -- Case studies.; elektronické knihy; electronic books